Effects of Iodixanol on Respiratory Functions during Coronary Angiography and the Role of Body Composition. (20th June 2018) - Guzel, Derya; Vural, Mustafa Gokhan; Akdemir, Ramazan
Abstract : Purpose . The purposes of this study are to assess the acute effects of iodixanol, an iso-osmolar contrast media, on pulmonary functions and to evaluate the body composition in order to find out its role in causing this deterioration. Methods . 35 male and 25 female patients undergoing diagnostic coronary angiography (CA) were enrolled in the study. Before CA, all patients' body compositions were evaluated by measuring their body mass indexes (BMIs) and waist-to-hip ratios (WHRs). Total body waters (TBWs), fat masses (FMs), fat-free masses (FFMs), and basal metabolism rates (BMRs) were measured via bioimpedance analysis. The CA was performed via radial artery route using iodixanol in every patient. The pulmonary function tests of these patients were performed before, during, and 2 hours after the CA. FEV1∆, FEF25–75% ∆, and FVC∆ parameters were calculated by subtracting the measured baseline value from the measurement after the CA. Results . Angiography caused significant reduction in forced expiratory volume in 1 sec (FEV1, from 94.17 ± 18.83 to 84.45 ± 18.31, p < 0.0001 ), forced vital capacity (FVC, from 96.57 ± 15.82 to 88.31 ± 17.96, p < 0.0001 ), and forced expiratory flow at 25–75% (FEF25–75% from 82.54 ± 24.26 to 72.11 ± 25.41, p = 0.001 ) and remained lower after 2 h after CA in male patients, respectively. FEV1 values were 103.40 ± 17.79 to 94.96 ± 17.063 (p = 0.004 ); FVC values were 107.20 ± 19.03 to 99.08 ± 20.56 (p = 0.009 ); and FEF25–75% values were 83.92 ± 24.30 to 73.24 ± 20.45 (p = 0.005 ) before and after CA and remained lower after 2 h after CA in female patients, respectively. FEV1/FVC ratio remained unchanged. FEF25–75% ∆ was statistically correlated with FFM, TBW, and WHR (p < 0.05 ;r = − 0.344, r = − 0.347, andr = 0.357, resp.), and FVC∆ was correlated with WHR in male patients (p = 0.018, r = 397 ). Conclusions . Our data suggested that diagnostic CA using iodixanol, an iso-osmolar contrast media, leads significant impairment in respiratory functions. Due to the persistence of these reductions even 2 hours after CA, ventilatory functions should be considered especially in patients whose body compositions or hydration levels are not within the desired physiological range.